Creating and Delivering Presentations Nano Tips with Jessica Chen. - Chen, Jessica (linkedin.com, 2022)
Get tips to prepare and deliver more effective, engaging presentations. Each video is less than two minutes long, so you can make learning fit into even your busiest days.